PENGEMBANGAN E-MODUL MATERI WUJUD ZAT DAN PERUBAHANNYA PADA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Effendi, Raimon; Estuhono, Estuhono; Rizki Handayani, Julia (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to develop a learning media to arouse students' enthusiasm in participating in the teaching and learning process or when carrying out learning evaluations in class IV science and science lesson content at Elementary School 03 Tiumang. Researchers use E-Module learning media (assisted by the Book Creator Application). The research in this writing takes the type of Research and Development (R&D) research, ADDIE has steps including Analysis Design, Development, Implementation and Evaluation. The type of data used is qualitative and quantitative data. It can be concluded as follows: 1) Development of E-Module learning media for Material Forms of Substances and Changes in Science and Science Lessons for class IV Elementary School 03 Tiumang (with the help of the Book Creator Application) using the ADDIE development model which can be tested in class IV Elementary School 03 Tiumang. 2) Validation of the E-Module learning media Material on Forms of Substances and Changes in Science and Science Lessons for class IV Elementary School 03 Tiumang (Assisted by the Book Creator Application) assessed by five validators. Validation shows that the E-Module learning media obtained a percentage of 87.25% with a very valid category. 3) The practicality assessed by the class IV guardian and students regarding the E-Module learning media obtained a percentage of 88,9% in the very practical category. 4) Effectiveness is assessed from student results. Student learning outcomes obtained a percentage of 95,6% in the very effective category.